"Teu meu corpo": Max Martins ou o amor das palavras - ARÁUJO, Jackeline Alves de (2020)
The present work is an analysis of the function of the unfolding of the linguistic signifier as body in the poem, through the erotic interlacing that is outlined in Max Martins' poetics, more precisely of its immanent aspects of a poetic-imagery, poetic-symbolic, poetic-ideographic . The erotic theory that is defined in the poetics of Max, takes into account the relation of the author-reader foreseen in the structures of seduction of the text of Max Martins. We have at stake a language operation that is properly semiotic, in fact, the theory of the desiring text of Roland Barthes is useful to us, since the author of The pleasure of the text (1973), in the relation that establishes between language and body operates for the purpose of enjoyment. The aesthetic objective of illustrating - beyond the limits of form and content - the erotic relation of words in copula, of the relation between author-reader-text, words make love.